2012
DOI: 10.3109/0886022x.2011.647301
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 and Endothelin A Receptor Immunoreactivity Is Increased in Patients with Diabetic Nephropathy

Abstract: In this preliminary report, the higher expressions of ET-1 and ET-RA found in both DN and IgA nephropathy suggest a potential role for the endothelin system in DN as well as in other nondiabetic glomerular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…It participates in podocyte dysfunction, inflammation and fibrosis and promotes mesangial cell proliferation and sclerosis. Increased staining for EDN1 in endothelial cells of glomerular and peritubular capillaries was observed in patients with diabetic nephropathy and IgAN compared with controls (Zanatta et al 2012). In our study, using the GeneGO Metacore software the possible involvement of NF-κB signaling in glomerular injury in patients with IgAN progression was proposed.…”
Section: Discussionmentioning
confidence: 59%
“…It participates in podocyte dysfunction, inflammation and fibrosis and promotes mesangial cell proliferation and sclerosis. Increased staining for EDN1 in endothelial cells of glomerular and peritubular capillaries was observed in patients with diabetic nephropathy and IgAN compared with controls (Zanatta et al 2012). In our study, using the GeneGO Metacore software the possible involvement of NF-κB signaling in glomerular injury in patients with IgAN progression was proposed.…”
Section: Discussionmentioning
confidence: 59%
“…Immunohistochemistry was chosen to detect ET‐1 in the laminar tissue, because it was shown that endothelial cells secrete 80% of ET‐1 abluminally in the direction of the tunica media . This method has successfully been used in kidney tissue of human patients with type 2 diabetes, where its higher expression compared with healthy control subjects was proved . One study on ET‐1 expression has used plasma concentration to monitor ET‐1 in clinically endotoxaemic horses ; however, this was not feasible in the present study owing to the need for repeated reservoir exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Hyperglycemia and impaired metabolic control may enhance vascular production of ET-1 in diabetes, which leads to glomerular damage by increasing vasoconstriction, mesangial cell proliferation and glomerular permeability. 12 Increased plasma concentration of ET-1 in patients with diabetes has been reported, 13,14 and a significant correlation has also been observed between plasma ET-1 levels and diabetic complications 15,16 but the relationship between ET-1 and indices of renal function is conflictive. It is known that patients with advanced chronic kidney disease or on dialysis have higher plasma concentrations of ET-1.…”
Section: Introductionmentioning
confidence: 99%